Coexistencia pacífica de explicaciones y reducción - Miguel, Hernán; Paruelo, Jorge (Revista de Filosofía, 2007)
The present paper deals with the notion of complementarity associated with Salmon’s proposal of peaceful coexistence between scientific explanation models. The relation between the coexistence of such models and theoretical reduction is studied. Finally a way of understanding peaceful coexistence is proposed which does not rely on pragmatic factors and also allows us to return to the use of the explanatory capacity of theories as a value of relevance in the rational choice between scientific theories.